Physiotherapy Management In Bilateral Knee Osteoarthritis By Providing Manual Therapy And Exercise Therapy: Case Report - Hidayah, Fenisa Nurul; Naufal, Adnan Faris; Pradana, Anas (FISIO MU: Physiotherapy Evidences, 2023)
Osteoarthritis of the knee is a degenerative disease that occurs in the joints and is progressive in nature which is characterized by damage to the cartilage structure which causes pathological changes in the joints. Symptoms that often arise are stiffness in the morning and there is also a "cracking" sound or also called a crepitus sound when making movements on the knee. Knee pain has an impact on various aspects of quality of life because it affects a decrease in functional activities such as squatting, standing, walking long distances, and going up and down stairs. The prevalence of Knee Osteoarthritis affects approximately 25% of adults and is currently increasing by 65% over the last 20 years. In this study the researchers conducted an intervention in the form of manual therapy for Mulligan Mobilization With Movement (MWM) and patella mobilization as well as exercise therapy in the form of stretching lower extremities, contract relax, quadriceps sets, active exercise and bridging exercise. The aim of the intervention was to reduce pain and increase functional activity in patients with Knee Osteoarthritis. The results of this study found a decrease in the level of pain intensity and a decrease in the disability score experienced by the patient.